Technological modernization of the national economy as an indicator of green finance: Data analysis on the example of Russia - Liudmila S. Kabir; Zhanna A. Mingaleva; Ivan D. Rakov (Green Finance)
BackgroundIn Russia, there is no publicly available information to analyze green finance, but companies claim significant amounts of raised funds that are labeled as green. Green finance and technological modernization are interrelated processes. Therefore, the focus of the research is to find an answer to the question: has green finance had an impact on the technological modernization of Russian industry? The goal is to find indicators that confirm the real, not imaginary, nature of green finance. The research method is based on statistical analysis with presentation of consolidated data in graphical and tabular form. Assessment of the degree of penetration of the green economy is carried out through analyzing the ongoing changes in the structure of industry.ResultsThe available green finance has not had an impact on the technological modernization of the Russian industry. The creation of a new green segment of the national financial market is blocked by the conservative structure of the economy.ConclusionsThe results of this study provide a methodological basis for the development of solutions on how to properly build the mechanism of accumulation of financial resources for the purposes of green transformation of the economy. Another significant contribution of our study is the convincing, empirically based and verifiable evidence that green economy and technological modernization are two sides of the same coin. Financing investment projects that do not lead to technological modernization is not green and generally sustainable financing.